Internet addiction and comorbid pyschiatric disorders in adolescents (Annals of Medical Research, 2021)
Aim: Internet addiction (IA) has become an increasing problem in adolescents. However, there are few studies conducted in clinical samples and examined comorbid psychiatric disorders in adolescents with IA. The aim of this study was to determine the sociodemographic characteristics and comorbid psychiatric disorders in adolescents with IA and to compare them according to gender.Material and Methods: This cross-sectional study was conducted with 80 adolescents aged 12-18 years. Participants with a Young Internet Addiction Scale score ≥ 50 were considered as internet addicts and were included in the study. Schedule for Affective Disorders and Schizophrenia for School Age Children-Present and Lifetime Version was used to evaluate psychiatric disorders.Results: The study was completed with 40 male and 40 female adolescents with IA. The mean age of the participants was 14.7. 83.3% of participants use the internet every day and 46.7% of participants use the internet more than six hours a day. The mean YIAS score of the participants was 63.0. All participants met criteria for at least one psychiatric disorder. The most common comorbid psychiatric disorders were depressive disorder (37.5%), ADHD (26.2%) and anxiety disorders (23.8%). When comorbid psychiatric disorders were compared according to gender, it was found that ADHD was significantly higher in boys and depressive disorder was significantly higher in girls.Conclusion: The results of the present study showed that adolescents with IA had a high rate of comorbid psychiatric disorders. Coexistence of addiction and psychiatric disorders has negative effects on the treatment of both addictions and psychiatric disorders. Therefore, all adolescents with IA should be evaluated for comorbid psychiatric disorders. Further studies are needed to explain the causal relationship between IA and psychiatric disorders.
Keywords: Adolescents; addiction; internet; psychiatric disorders; ADHD; depressive disorder; anxiety disorder